2021
DOI: 10.1007/s10803-020-04816-6
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Impact of COVID-19 on Individuals with ASD and Their Caregivers: A Perspective from the SPARK Cohort

Abstract: The impact of the 2019 coronavirus pandemic (COVID-19) in the United States is unprecedented, with unknown implications for the autism community. We surveyed 3502 parents/caregivers of individuals with an autism spectrum disorder (ASD) enrolled in Simons Powering Autism Research for Knowledge (SPARK) and found that most individuals with ASD experienced significant, ongoing disruptions to therapies. While some services were adapted to telehealth format, most participants were not receiving such services at foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
149
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(171 citation statements)
references
References 20 publications
16
149
0
6
Order By: Relevance
“…These issues include the impact of isolation; changes in education and employment; public understanding of adjustments to regulations for autistic people; and, now, how earlier policies have impacted on the accessibility of vaccination programmes and strategies. In particular, the mental and physical health impacts of COVID-19 should be assessed, given high reported rates of pandemic-related stressors among families with a child with autism, [104][105][106] and possible long-term mental and physical health implications of COVID-19 infection. 107 108 Furthermore, longitudinal data on health and social care access and the impact of disruptions to education and community facilities before, during and after the COVID-19 pandemic may reveal critical areas for addressing future policy and practice.…”
Section: Learning From Best Practice and Future Directionsmentioning
confidence: 99%
“…These issues include the impact of isolation; changes in education and employment; public understanding of adjustments to regulations for autistic people; and, now, how earlier policies have impacted on the accessibility of vaccination programmes and strategies. In particular, the mental and physical health impacts of COVID-19 should be assessed, given high reported rates of pandemic-related stressors among families with a child with autism, [104][105][106] and possible long-term mental and physical health implications of COVID-19 infection. 107 108 Furthermore, longitudinal data on health and social care access and the impact of disruptions to education and community facilities before, during and after the COVID-19 pandemic may reveal critical areas for addressing future policy and practice.…”
Section: Learning From Best Practice and Future Directionsmentioning
confidence: 99%
“…April is Autism Awareness month, yet in the spring of 2020, COVID-19 dominated the headlines and mental health leaders acknowledged the significant changes impacting the daily lives of individuals in the autism community (Gordon & Borja, 2020), warning that alteration of routines can lead to increased stress and difficulty coping. A brief online survey of parents (93% female) of children with ASD (80% male, mean 12-years, 21% had ASD, and intellectual disability) reported that despite some positive impact of social distancing, families experienced significant upheaval (White et al, 2021). While such surveys are helpful, it is imperative that evidence be collected during the pandemic via rigorous approaches to learn directly from individuals with autism and their care providers to better prepare for future outbreaks (Courtenay & Perera, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date only a few studies (Ersoy et al, 2020;Esentürk, 2020;Mannging et al, 2020;Pavlopoulou et al, 2020;Stankovic et al, 2020;White et al, 2021), to our knowledge, have described the mental health and well-being of caregivers of autistic people during the pandemic. Manning and colleagues (2020) investigated the COVID-related experiences of 471 autistic individuals and their families in the United States using an online survey.…”
mentioning
confidence: 99%